PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP PERKALIAN MENGGUNAKAN MODEL OPEN ENDED KELAS III SD NEGERI 03 ALAI TIMUR - Nesta Olivia (STKIP Subang, 2022)
This research was motivated by the low understanding of students' concept of multiplication in class III SD Negeri 03 Alai Timur. Learning directly to symbols and formulas makes it difficult for students to understand mathematical concepts, especially in multiplication. Students find it difficult to solve multiplication problems. In addition to the problems above, students' understanding of concepts is also lacking, because students have not been facilitated by learning models that involve active students in learning. All of these problems have an impact on low student learning outcomes related to multiplication. In general, the purpose of this study was to describe the increase in students' understanding of concepts in multiplication learning. This research is a classroom action research with a qualitative and quantitative approach. The subjects in this study were third grade students at SD Negeri 03 Alai Timur. This study consisted of II cycles, cycle I held 2 meetings and cycle II 1 meeting consisting of planning, implementation, observation and reflection. The data collection technique is observation and documentation. While the research instrument is the observation sheet and documentation. The results showed that the success criteria for understanding the concept of students in the first cycle of the first meeting was 58.23%. meeting II 86.823%. Cycle II meeting I was 87.04%. Thus the use of the open ended model in multiplication learning in class III SD Negeri 03 Alai Timur can improve students' understanding of concepts.